Natural history of intraosseous low-grade chondroid lesions of the proximal humerus - LaPrade, Christopher M.; Andryk, Logan M.; Christensen, Joshua L.; Neilson, John C.; Wooldridge, Adam N.; Hackbarth, Donald A.; Bedi, Manpreet; King, David M. (Frontiers in Oncology, 2023)
Enchondromas and grade 1 chondrosarcomas are commonly encountered low-grade chondroid tumors in the proximal humerus. While there is a concern for malignant transformation, few studies have evaluated the natural history of these lesions. The purpose of this study is to evaluate the natural history of proximal humerus low-grade chondroid lesions managed both conservatively and surgically, and to define management criteria using clinical and radiographic findings for these low-grade chondroid lesions. The patient population included 90 patients intended for conservative treatment and 22 patients proceeding directly to surgery. Data collection was based on a combination of chart review and patient imaging and descriptive statistics were calculated for each group. No malignant transformations were noted amongst any group. In the conservative treatment group, 7 of 64 (11%) progressed to surgery after an average of 20.3 months of conservative treatment due to persistent pain unexplained by other shoulder pathology. Importantly, 71% experienced continued pain at a mean of 53.1 months postoperatively. The group that went directly to surgery also demonstrated pain in 41% at an average follow-up of 57.3 months. Low-grade cartilaginous lesions of the proximal humerus without concerning imaging findings can be managed with conservative treatment and the risk of malignant transformation is very low. Patients with a clear source of their shoulder pain unrelated to their tumor and without concerning characteristics on imaging can be managed with serial annual radiographic imaging. Patients undergoing surgery for these indolent tumors are likely to experience persistent pain even after surgery.